2016
DOI: 10.1049/mnl.2016.0518
|View full text |Cite
|
Sign up to set email alerts
|

Stacked piezoelectric energy harvesting device by printing process

Abstract: A simple printing process to design a novel piezoelectric energy-harvesting device made from vinylidene fluoride/trifluoroethylene copolymers is presented. Fabrication using a metal nanoink and a household printer dramatically reduced the fabrication complexity. In addition, this process employed low-temperature steps, and thus the structural damage to the polymers resulting from high-temperature annealing was avoided. By stacking the devices and connecting them in parallel, the generated energy was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The final morphology and structures of P(VDF-TrFE) highly depend on the annealing temperature (T a ). [58][59][60][61][62][63][64][65][66] The annealing is usually performed in a temperature range between the glass transition temperature (T g ) and the melting temperature (T m ) of the polymer, that is, T g < T a < T m . There is, however, an optimal annealing temperature for a polymer.…”
Section: Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…The final morphology and structures of P(VDF-TrFE) highly depend on the annealing temperature (T a ). [58][59][60][61][62][63][64][65][66] The annealing is usually performed in a temperature range between the glass transition temperature (T g ) and the melting temperature (T m ) of the polymer, that is, T g < T a < T m . There is, however, an optimal annealing temperature for a polymer.…”
Section: Annealingmentioning
confidence: 99%
“…The annealing treatment along with thickening of lamellae and enlarging crystalline grain size plays an important role on enhancing the crystallinity (Figure 2A). The final morphology and structures of P(VDF‐TrFE) highly depend on the annealing temperature ( T a ) 58–66 …”
Section: Influencing Factors On the Crystallinitymentioning
confidence: 99%
“…At present, there are many studies on piezoelectric energy harvesters. The common energy harvesters are cantilever beam type [11][12][13][14][15], cymbal type [16][17][18], multilayer stack type [19,20], bridge type [21,22], arch type [23][24][25], etc., and there are new energy harvesters [26][27][28][29] 2,201,2424 made of composite materials, such as piezoelectric fiberboard (MFC), polyvinylidene fluoride (PVDF), and piezoelectric film.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a simple fabrication process for a VDF=TrFE copolymer harvester, which circumvents the sputter and vapor deposition processes, to address these issues. 11) In this study, we investigated a VDF=TrFE copolymer film to fabricate an energy harvester, which could be actuated without polling, by controlling the polymer film thickness. We found that the crystallinity of the VDF=TrFE copolymer is affected by its thickness by observing the polymer crystallization by Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) analysis.…”
mentioning
confidence: 99%